Relative performance of old and newly released yam varieties in hydroponics system for seed yam production - Balogun, M.; Ekundayo, M.; Ossai, C.; Jimoh, L.; Maroya, N.; Aighewi, B.; Mignouna, D.; Amele, A.; Legg, J. (2023)
Rapid multiplication of improved yam varieties is crucial to enhance farmers’s access to seeds. Seed yam production has been enhanced using hydroponics system. However, reports on use of hydroponics have been for few improved genotypes released at least one decade ago. This study assessed the amenability of released / near-release yam genotypes to hydroponics substrates. Two weeks old Breeder seedlings of three released varieties of Dioscorea alata (Akuabata, VaYam and Wonder) and four genotypes of Dioscorea rotundata (Released: Kpamyo and Asiedu, and near-release: Danacha and Meccakusa) were planted in the following hydroponics susbtrates; Riversand, Riversand+Ashed Ricehusk (RS+AH: 3:1), Cocopeat, Cocopeat+Ashed Ricehusk (CP+ASH: 3:1) and Ash. Fertigation was daily with nutrient solution as described previously. Data were taken on the Number of Single Node Vine Cuttings (SNVC) f rom 18 stands at 2 Weeks after Planting (WAP), Percentage Vine Survival (PVS), Number of Nodes (NON) at 6WAP, Number of Tubers (NOT) and Tuber Weight (TW) g at harvest. Data were analysed using ANOVA , and means were separated using Least Signif icant Differences at P=0.05. The SNVC, PVS, NON, NOT and TW of the genotypes differed signif icantly and ranged from 220 (Wonder) to 596 (Asiedu), 33.8% (VaYam) to 95.4% (Danacha), 16.0±1.4 (Danacha) to 35.1±1.4 (Asiedu), 1.4±0.1 (Danacha) to 1.9±0.1 (Akuabata), and 16.6±2.6g (Wonder) to 40.3±2.6g (Asiedu), respectively. The substrate effect on SNVC, PVS, NON, NOT and TW ranged f rom 143 (CP+AH) to 577 (RS+AH), 42.7% (CP+AH) to 60.9% (Riversand), 4.33±1.1 (Ash) to 30.3±1.1 (RS+AH), 1.0±0.1 (Ash) to 2.1±0.1 (RS+AH), and 1.4±2.3g (Ash) to 50.3±2.3g (Riversand), respectively. Genotype by substrate interactions were also signif icant. Asiedu gave the highest vine production in the hydroponics system relative to the near release varieties, but the near-release varieties Danacha and Akuabata had higher vine survival rate and number of minitubers, respectively. The implications of these f findings in evolution of the formal yam seed system are discussed.